A Treatable Cause of Progressive Visual Loss - Susan Abraham Miny; Gladson Nikhil (International Journal of Neuroimaging, 2023)
Sphenoethmoidal encephalocoele is a rare clinical entity with varying clinical presentation. It can be seen in association with corpus callosal agnesis and midline facial defects. We are reporting a case of 44 year old female presented with progressive vision loss of right eye, and surgical correction of meningoencephalocoele and the defect prevent further visual detiortion.
Keywords: MRI